EVALUASI PENYELENGGARAAN DIKLAT DI KEMENTERIAN AGAMA - Farida Hanun, M.Pd (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2018)
AbstractThis paper aims: (i) to study the quality of the training and education program results (ii) to evaluate input, process, and product, and (iii) to formulate the policy strategy of the training and education program administration. The study used qualitative method through a CIPP (Context, Input, Process, Product) evaluation approach and was held at the Centre of Training and Education Program (Pusdiklat) and seven training and education halls (balai diklat) in Ministry of Religious Affairs. Data collection was obtained through questionnaire, interview, and literature study. Results showed the quality of the input components and the training and education program administration are categorized as Average (Cukup). Meanwhile, the output component (i.e. participant) is still categorized as Low (Rendah). Therefore, the Ministry of Religious Affairs is recommended: (i) to improve the participant recruitment system, (ii) to improve the trainers’ quality, (iii) to innovate the program curriculum, (iv) to serve the infrastructure for the training program, and (v) to encourage the technical training and education institution in attending the accreditation program held by the State Administration Agency (Lembaga Administrasi Negara, LAN), as an effort to improve the quality.Abstrak Tulisan ini bertujuan untuk  mengevaluasi kualitas hasil diklat aspek input, proses dan produk serta merumuskan strategi kebijakan penyelengraan diklat. Studi ini menggunakan metode kualitataif dengan pendekatan evaluasi Contex, Input, Procces, Product (CIPP) dan dilaksanakan di Pusat Pendidikan dan Pelatihan (Pusdiklat) dan 7 Balai diklat di lingkungan Kementerian Agama. Pengumpulan data menggunakan kuesioner, wawancara dan Studi Kepustakaan. Hasil studi menunjukkan bahwa  kualitas komponen input dan proses penyelenggaraan diklat dikatagorikan cukup. Sedangkan komponen output (peserta diklat)  masih berkualitas rendah. Oleh karena itu direkomendasikan agar Kementerian agama memperbaiki sistem rekruitmen peserta diklat, meningkatkan kualitas widyaiswara, melakukan inovasi kurikulum diklat, melengkapi sarana prasaana kediklatan dan mendorong lembaga diklat teknis mengikuti akreditasiyang diselenggarakan oleh  Lembaga Administrasi Negara (LAN) dalam upaya peningkatan kualitas.